FORMULATION AND EVALUATION OF TRANSDERMAL PATCH OF INDOMETHACIN CONTAINING CARDAMOM OIL AS PERMEATION ENHANCER - Krishnamurthy A. Kamalapurkar,; Fariyal N. Shaikh, (EPRA International Journal of Research and Development (IJRD), 2022)
Transdermal drug delivery system are innovative drug delivery system which is effective for achieving efficient systemic effect by passing hepatic first pass metabolism. Transdermal patches of Indomethacin were prepared by the solvent casting evaporation technique using ethyl cellulose, HPMC, dibutyl phthalate and cardamom oil as permeation enhancer using different ratios. The physicochemical parameters such as flexibility, thickness, weight variation, moisture content, folding endurance and content uniformity were evaluated for the prepared patches. The formulation exhibited flexibility, uniform thickness and weight, smoothness, good drug content (82.1 to 98.8%), and little moisture content. The in vitro diffusion studies were carried out using modified Franz diffusion cell using Cellulose acetate membrane filter(0.45/0.47mm) as the diffusion membrane. As polymer increases the drug release decreases. In this research work cardamom oil used as penetration enhancer, and it shows good release as certain time intervals. Among all three formulations F3 formulation showed good drug release i.e 98.8%.